B cell activation through CD40 and IL4R ligation modulates the response of chronic lymphocytic leukaemia cells to BAFF and APRIL. (18th November 2013) - Ferrer, Gerardo; Bosch, Rosa; Hodgson, Kate; Tejero, Rut; Roué, Gael; Colomer, Dolors; Montserrat, Emili; Moreno, Carol
Summary The two tumour necrosis factor family proteins BAFF (TNFSF13B) and APRIL (TNFSF13) and their receptors [BAFF‐R (TNFRSF13C), TACI (TNFRSF13B), BCMA (TNFRSF17)] play a critical role in the survival of normal B cells. The sensitivity of normal B cells to BAFF and APRIL can be modulated by signals regulated by their receptors. This modulation, however, has not been extensively investigated in chronic lymphocytic leukaemia (CLL) cells. We evaluated the expression, regulation and signalling of BAFF and APRIL receptors in normal and in CLL cells upon stimulation through CD40+IL4R and BCR. We further analysed the prognostic value of BAFF and APRIL receptors expression in patients with CLL. BCMA expression was significantly higher on CLL cells than on normal B cells. BCR and CD40+IL4R stimulation promoted an increase in TACI and BCMA expression, cell viability and activation in normal B cells. A similar effect was observed in CLL cells after CD40+IL4R but not BCR stimulation. BCMA expression correlated with unmutated IGHV genes, poor‐risk cytogenetics, and short progression‐free survival. These findings further characterize the link between CD40+IL4R regulatory signals, BAFF, APRIL and their receptors and the survival of leukaemic cells and clinical features of CLL.